Effect of imidazolium based silver nanoparticle irrigant on root canal dentin roughness in comparison with three common irrigants - Farshad, Melika; Abbaszadegan, Abbas; Ghahramani, Yasamin; Jamshidzadeh, Akram (Iranian Endodontic Journal, 2016)
Introduction: The aim of this study is to evaluate the effect of a newly introduced nanosilver based irrigant on dentin roughness in comparison with three commonly used root canal irrigants. Material and methods: Irrigants tested were: NaOCl 5.25%, EDTA 17%, CHX 2% and newly introduced imidazolium-based silver nanoparticle (Im AgNP) irrigant at 5.8×10 -8 mol/L. Distilled water was used as control. Roots of 25 human anterior teeth were sectioned longitudinally to obtain 50 dentin samples. Roughness values were evaluated by Atomic Force Microscopy analysis on 5 groups of 10 samples after each group were treated in one of the tested irrigant solutions for 10 minutes. Results: Dentin roughness significantly increased from 95.82 nm (control) to 136.02 nm, 187.07 nm, 142.29 nm and 150.92 nm by NaOCl, CHX, Im AgNP irrigant and EDTA respectively. CHX demonstrated a significantly higher roughness value compared to the other irrigants tested while no significant differences were seen in NaOCl, Im AgNP irrigant and EDTA groups. (P>0.05) Conclusions: Im AgNP irrigant affect physicochemical property of dentin and raised its surface roughness, thus, this irrigant could impact bacterial and restorative material adhesion to root canal dentin walls.